2009
DOI: 10.5194/angeo-27-2399-2009
|View full text |Cite
|
Sign up to set email alerts
|

Joint observations of a traveling ionospheric disturbance with the Paratunka OMTI camera and the Hokkaido HF radar

Abstract: Abstract. On 10 September 2007 between 10:00 and 14:00 UT, the OMTI all-sky imager at Paratunka (Kamchatka, Russia, GLAT∼52 • ) observed the onset and southwestern progression of a localized depletion region in the airglow intensity. The perturbation, while being stretched in the NW-SE direction, crossed the entire field of view of the camera. During the event, the Hokkaido SuperDARN HF radar was monitoring echoes in the Paratunka longitudinal sector. It was detecting a localized band of ground scatter echoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In such conditions, concurrent observations with other instruments such as optical imagers and/or GPS TEC receivers are extremely useful. For example, Shiokawa et al (2008) and Koustov et al (2009) reported HOK GS echo bands moving equatorward in unison with optically identified MSTIDs. Finally, Oinats et al (2015) found nighttime mid-latitude MSTIDs are less frequent in winter; however, this may be due to a general decrease in GS occurrence because optical observations show clear MSTID maxima at solstices (Duly et al 2013 and references therein).…”
Section: Nighttime Mstids: Introductionmentioning
confidence: 99%
“…In such conditions, concurrent observations with other instruments such as optical imagers and/or GPS TEC receivers are extremely useful. For example, Shiokawa et al (2008) and Koustov et al (2009) reported HOK GS echo bands moving equatorward in unison with optically identified MSTIDs. Finally, Oinats et al (2015) found nighttime mid-latitude MSTIDs are less frequent in winter; however, this may be due to a general decrease in GS occurrence because optical observations show clear MSTID maxima at solstices (Duly et al 2013 and references therein).…”
Section: Nighttime Mstids: Introductionmentioning
confidence: 99%
“…Occurrence of nighttime medium‐scale traveling ionospheric disturbances (MSTIDs) is a common feature of the ionosphere over Japan [e.g., Yamamoto et al ., ; Shiokawa et al ., ; Saito et al ., ; Ogawa et al ., ]. MSTIDs have been observed with optical imagers [ Shiokawa et al ., ; Otsuka et al ., ], GPS receivers sensitive to the total electron content (TEC) in the ionosphere [ Saito et al ., ], HF radars [ Ishida et al ., ], and combination of these instruments [ Koustov et al ., ; Ogawa et al ., ; Suzuki et al ., ; Hayashi et al ., ; Ichihara et al ., ]. It has been established that nighttime MSTIDs over Japan propagate with the speeds in the range of several tens of meters per seconds to ~150 m/s predominantly in the SW direction.…”
Section: Introductionmentioning
confidence: 98%
“…SuperDARN observations of MSTIDs through ground scatter allowed estimating the magnitude of electron density perturbations in the ionosphere [ Bristow and Greenwald , ]. SuperDARN studies of MSTIDs using ground scatter at midlatitudes have been limited mostly to the Japanese sector [ Ishida et al ., ; Ogawa et al ., ; Koustov et al ., ; Ichihara et al ., ] where some differences with high‐latitude counterparts have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second midlatitude SuperDARN radar has been operative in Hokkaido, Japan since December 2006. The radar was found to be a very powerful tool for monitoring storm time high‐speed subauroral flow [ Ebihara et al , 2008; Kataoka et al , 2007, 2009; Koustov et al , 2008] and various thermospheric waves [ Ishida et al , 2008; Ogawa et al , 2009; Suzuki et al , 2009; Koustov et al , 2009]. Since the radar field of view (FOV) well covers the possible source region of DUSE at the subauroral latitudes, the radar is suitable for estimating the latitudinal extent of DUSE.…”
Section: Introductionmentioning
confidence: 99%